PENERAPAN MODEL PBL BERBANTUAN MEDIA PAPEDA (PAPAN PEMANFAATAN PELESTARIAN SDA) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SDN PUNTEN 01 BATU - Alifvia, Bunga Cika; Restian, Arina; Siswanto, Ernaz (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research aims to implement a PBL (Problem Based Learning) model using PAPEDA (Board for Conservation and Utilization of Natural Resources) to improve fifth-grade students' learning outcomes at SDN Punten 01 Batu. This addresses unsatisfactory results in Natural Science, particularly regarding natural resource conservation and use. Observations revealed a lack of concrete examples and student-centered learning. The study comprises four stages: planning, implementation, observation, and reflection. Data collection uses observation and tests, with evaluation questions as instruments. The subjects are 22 fifth grade students at SDN Punten 01 Batu. Findings prove that the PBL model with PAPEDA improves student learning outcomes. Average scores increased from 77.2 with 68% classical completeness in cycle I to 82.7 with 86.3% classical completeness in cycle II. The study concludes that applying the PBL (Problem Based Learning) model assisted by PAPEDA concrete media effectively enhances learning outcomes for fifth-grade students at SDN Punten 01 Batu.